What chance do we have to decrease prostate cancer overdiagnosis and overtreatment? A narrative review - Ziglioli, Francesco; Granelli, Giorgia; Cavalieri, Domenico; Bocchialini, Tommaso; Maestroni, Umberto (Acta Biomedica Atenei Parmensis, 2019)
In the era of biochemical tests and algorithms, the management of prostate cancer from prevention to treatment is still controversial. The debate is focused on clinically-significant and clinically-insignificant prostate cancer. As it is well known, the diagnostic tools available are not able to distinguish between the two, thus leading to men treated for prostate cancer even if not strictly necessary. Unfortunately, as of today, there is no test available able to predict the clinical aggressiveness of prostate cancer at the time of the diagnosis. However, some indexes, PSA derivatives, immunocomplexes, and diagnostic methods have been proposed. If properly used in the daily clinical practice, these tools may be of support in the decision making process, in the effort to reduce the overdiagnosis and the overtreatment of prostate cancer.For this reason, we believe that a clear knowledge of this tools, indexes and diagnostic methods is of the utmost importance in preventing the morbidities related to unnecessary treatment as weel as preventing the detrimental effect of missing the diagnosis of a clinically significant prostate cancer.This reviews encompasses the most studied tests and diagnostic methods to predict the aggressiveness of prostate cancer, to avoid to miss a diagnosis of clinically significant cancers and to optimize the overall pre-treatment work-up. (www.actabiomedica.it)